If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-17-2x=-6x
We move all terms to the left:
-17-2x-(-6x)=0
We get rid of parentheses
-2x+6x-17=0
We add all the numbers together, and all the variables
4x-17=0
We move all terms containing x to the left, all other terms to the right
4x=17
x=17/4
x=4+1/4
| 2(3a-7)=13 | | 5n+2n=92 | | 5x+8=6(x+4) | | 7(1-3x)=9x-53 | | 9x-15=6x-12 | | v−–22=88 | | 7s-19-10s=13+s | | 5d-8=4+7d | | 3v−2=7 | | 9a−7a=3a−33+2a | | –3c+11c=–16 | | 24=v+14 | | -7y+7=24y-4 | | 2x+7−5x+8=3(5+6x)−12x= | | 50=40a | | 5/6x+21=1/6x+17 | | 6(3-x)=6 | | 4x+12-6x=16 | | -9-9-5f=-8f+9 | | -2x-(1/2)=1/4 | | -180=-8k-5(4K+8) | | 2(z-8)=2 | | -7(-3-x)=-2(2-x) | | -6(b+3)+6b=6b=-6(-4b+3) | | k/8=0.8k= | | 6(4+5a)+10a=-10(1-6a)-6 | | 3(–4z+6)=–(12−6z) | | 18-3t=-12 | | -20k-13k+-11=10 | | 8(x+9)=72-5x | | 2k+18=0 | | 12(n)=5n-6 |